Production of Light Weight Foam Concrete with Sustainable Materials - Ali, A. W.; Fawzi, N. M. (Engineering, Technology & Applied Science Research, 2021)
Most of the recent works related to the construction industry in Iraq are focused on investigating the validity of local raw materials as alternatives to the imported materials necessary for some practical applications, especially in thermal and sound insulation. This investigation includes the use of limestone dust as partial substitution of cement in combination with foam agent and silica fume to produce sustainable Lightweight Foam Concrete (LWFC). This study consists of two stages. In the first stage, trial mixes were performed to find the optimum dosage of foam agent. Limestone dust was used as a partial replacement for cement. Chemical analysis and fineness showed great similarity with cement. Many concrete mixes were prepared with the content of lime dust powder being 10%, 14%, and 18% as partial replacement of cement by weight. The results indicate that the compressive strength at 7, 28, and 90 days of age was increased for specimens with 14% limestone dust. The best results in compressive strength show an increase at 7 days and a decrease at 28 and 90 days for concrete specimens with 14% limestone dust. In addition, the results show a decrease in dry density for concrete containing 14% lime dust. In the second stage, different percentages of Polypropylene Fibers were added to the concrete, all mixes, containing a constant content of limestone dust of 14% by weight of cement, were modified using different percentages of Polypropylene Fibers (1%, 1.5 %, and 2% by volume) and the best percentage was found to be 1%. The addition of Polypropylene Fibers enhances splitting tensile and flexural strength at 28 days by 14.55% and 55% respectively.